The Song of an Innocent Bystander - Bone, Ian 1956- (New York : Dutton Books, 2004)
With the approach of the tenth anniversary of the time she was held hostage in a fast food restaurant, nineteen-year-old Freda Opperman struggles to make sense of her memories of the event and how they have shaped her life.
Accelerated Reader AR